Synthesis of some new 1,3,5-trisubstituted pyrazoles as antioxidant and antiinflammatory agents - Arora, Pragi; Dua, Jagdeep; Singh, Jitender (Journal of Drug Delivery and Therapeutics, 2019)
A series of some new 1,3,5-trisubstituted pyrazoles was synthesized by the reaction of α-β dibromochalcones with phenylhydrazine hydrochloride. α-β-Dibromochalcones were prepared by the regioselective bromination of respective chalcones with tetrabutylammonium tribromide. The synthesized trisubstituted pyrazoles were evaluated for their anti-inflammatory and antioxidant properties. Keywords: α-β-Dibromochalcones, 1,3,5-Trisubstituted pyrazoles, Tetrabutylammonium tribromide, Anti-inflammatory and antioxidant activities